Hedges Expressions in Confessional Discourse of Ida Craddock’s Suicide Notes - Bahar, Rizkya Fajarani; Ariyanti, Lisetyo (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2020)
Some people commited suicide tried to express what they felt and left message explaining the causes of why they committed suicide. The suicide note was written by the person who commited suicide as a purpose to give a sign to other people. One of those people was Ida Craddck who was a 19th century American. She advocated freedom of speech and women rights who committed suicide because of inappropriate decision from the judge. Her books were prosecuted by Anthony Comstock as obscene literature. This study was aimed to examine the hedges expressions that maintained the functions of confessional texts which were used by Craddock. The results found that hedges were used on her confessions to support her criticism and wish to the public. Those criticism and wish were confessed by Craddock to aware the public about people’s freedom condition. Her confessions had function to tell her personal story that led her to suicide which could be learnt by other people so that they could have a better life. Finally, hedges were used to express her uncertainty of the truth of what she confessed about her cause of death.